Implementasi Program Festival Anak Sholeh ddalam Mendukung Moderasi Beragama dan Penguatan Kerukunan Umat di Desa Bangun Purba - Nasution, Yanisa; Febriyanti, Chairina; Husein, Ismail; Ritonga, Muhammad Iqbal; Harahap, M. Rivan Febriansyah; Pratidina, Maulia; Saragih, Dewi Kentri (Civiliza Publishing, 2025)
Religious moderation is an important pillar in maintaining harmony in the midst of Indonesia's diversity. Through the Real Work Lecture (KKN) program, UIN North Sumatra students of the Bangun Purba Village group held the Sholeh Children's Festival as a means of strengthening religious moderation and love for humanity. This study aims to describe the implementation, methods, and impacts of these activities. The method used is a participatory approach by involving the community from planning to implementation. Activities in the form of Islamic competitions such as the adhan, memorization of short surahs, Islamic coloring, Islamic poetry, and prayer with the participation of elementary school children as well as the support of parents, religious leaders, and village officials. The results showed a positive response with high enthusiasm from participants and the community. Activities have an impact on increasing courage, motivation to learn religion, and children's creativity; for the community to strengthen social relations and concern for religious education; and for students to provide direct experience in the implementation of religious moderation, social skills, and leadership.